Cocoa Powder Antioxidant Activity Test Using Cyclic Voltammetry and Differential Pulse Voltammetry Methods - Anis Sakinah; Ibrahim Dhuafa Fikri (Chemistry and Materials, 2023)
The main antioxidant compounds contained in cocoa are polyphenols, including flavonoids such as epicatechin, catechin, and procyanidin. This study aims to determine the antioxidant activity of three samples of cocoa powder using 1,1-diphenyl-2-picrylhydrazyl (DPPH) as a free radical by electroanalytical methods, namely cyclic voltammetry (CV) and differential pulse voltammetry (DPV). From the CV information obtained, the first anodic peak from DPPH appears at a potential of 0.33 V with an anodic current of 2.75 A/cm2, while the first anodic peak at DPPH after adding the chocolate sample which has the highest antioxidant activity appears at a potential of 0.43 V with an anodic current of 4.60 A/cm2. From the DPV information obtained, the anodic peak of DPPH appears at a potential of 0.19 V at an anodic current of 2.11 mA, while the anodic peak at DPPH after adding the chocolate sample which has the highest antioxidant activity appears at a potential of 0.02 V at an anodic current of 1.97 mA. The results show that the electroanalytical method has the potential to analyze the antioxidant activity of cocoa powder samples.